Methane Production From Industrial Hemp - Aleksandrs M. Adamovics; Semjons A. Ivanovs; Vilis S. Dubrovskis (Сельскохозяйственные машины и технологии)
Abstract. Due to the increasing shortage of fossil fuels, the use of alternative energy sources is becoming even more popular. In Latvia, maize is predominantly used for the production of biogas, and other crops are being studied for this purpose. (Research purpose) To study the productivity of industrial hemp varieties (Cannabis sativa L.) and the possibility of obtaining biogas from hemp. (Materials and methods) Field experiments on hemp productivity were carried out on sod calcareous, heavy dusty sand clay soils in 2012-2014. Ten industrial varieties of hemp – 'Bialobrzeskie', 'Futura 75', 'Fedora 17', 'Santhica 27', 'Beniko', 'Ferimon', 'Epsilon 68', 'Tygra', 'Wojko', and 'Uso 31' – were sown with a seeding rate of 50 kilogram per hectare at the background of fertilizers: nitrogen – 120, phosphoric oxide – 90, potassium oxide – 150 kilogram per hectare. Hemp was sown on 10-square meter plots in mid-May, in triplicate. Hemp was harvested at the beginning of seed ripening phase. The whole crop of green mass was calculated on a completely dry matter. The fermentation process for the production of biogas, the average yield of methane, and other parameters were studied in the Laboratory of Bioenergetics of the Latvia University of Life Sciences and Technologies, using small-sized bioreactors. (Results and discussion) The dry matter yield of hemp obtained in the agro-climatic conditions of Latvia averaged 13.32- 17.78 tons per hectare. For an average of three years (2012-2014), higher yields of dry matter were obtained from the varieties of 'Futura 75' (17.76 tons per hectare) and 'Tygra’ (16.31 tons per hectare). The average amount of methane obtained from the 'Uso 31' leaves was 0.365 litre from one gramme of dry organic matter, which is a very good result as compared to other energy crops, for example, corn silage (0.319-0.330 litre from one gramme of dry organic matter in Latvia). (Conclusions) The research has demonstrated that hemp can be successfully used to produce biogas, and hemp leaves are the most suitable starting material.